Process plants : a handbook for inherently safer design. - Kletz, Trevor A. (CRC Press/Taylor & Francis, 2010)
This resource covers the design of inherently safer and user-friendly plants. It demonstrates how chemical plants can withstand human error and equipment failures without serious effects on safety, output, or efficiency.